Comparison the effects of two different manufacturing techniques on the fracture strength of lithium disilicate crystal_reinforced glass ceramic crowns ( in vitro study ) - سلوم, زين العابدين; ريمة صقر (Latakia University Journal -Medical Sciences Series, 2023)
Aim: the aim of the study is to evaluate the effects of manufacturing techniqhes (ips press ,ips cad) on the fracture strength of ceramic crowns made by lithium disilicate crystal_reinforced glass ceramic Materials and Methods: The research sample consisted of 28 upper first premolar free from caries and fissures, with similar sizes, all of them were preserved with physiological serum at a concentration of 0.9% and at room temperature from the moment of extraction, after being properly cleaned. The sample was randomly divided into two main groups. Each of them has 14 premolar, where the first main group received 14 ceramic crowns made of lithium disilicate crystal-reinforced glass ceramic using the heat press technique ( ips press), after preparing the teeth of this group according to the academic protocol adopted in preparation for receiving full ceramic crowns, and the second main group received 14 ceramic crowns made of lithium disilicate crystal-reinforced glass ceramic using the Cad/Cam technique (IPS CAD), after preparing the teeth of this group according to the approved academic protocol adopted in preparation for receiving full ceramic crowns, all the crowns were adhesved to their abutments using resin cement according to the academic protocol adopted in Gluting glass ceramic crowns , then we divided each main group into two sub-groups of 7 crowns each, in order to study the effects of vertical forces (90 degrees) on the fracture strength of the crowns belong to the first sub-group and the inclined forces (45 degrees) on the fracture strength of the crowns belong to the second sub-group and This is done by universal testing machine Results: there are statistically significant difference in the fracture strength between crowns manufactured using the heat press technique and crowns manufactured using cad\cam technique, where the average fracture strength of the crowns manufactured using the press technique was 1816,71 N ,1154,61 N when applying both vertical forces and oblique forces at an angle of 45 degrees respectively, While the average fracture strength of crowns made using CAD\CAM technology was 1944,17 N, 1243,1N when applying both vertical forces and oblique forces at an angle of 45 degrees respectively Conclusions: The CAD\CAM technology provided a higher fracture strength than the heat press technique in the manufacture of full ceramic crowns made by lithium disilicate crystal_reinforced glass ceramic , and The fracture strength values were higher when applying vertical forces (90 degrees) compared to the oblique forces (45 degrees).